Role of the Nucleus as a Sensor of Cell Environment Topography. Issue 8 (28th December 2017) - Anselme, Karine; Wakhloo, Nayana Tusamda; Rougerie, Pablo; Pieuchot, Laurent
Abstract: The proper integration of biophysical cues from the cell vicinity is crucial for cells to maintain homeostasis, cooperate with other cells within the tissues, and properly fulfill their biological function. It is therefore crucial to fully understand how cells integrate these extracellular signals for tissue engineering and regenerative medicine. Topography has emerged as a prominent component of the cellular microenvironment that has pleiotropic effects on cell behavior. This progress report focuses on the recent advances in the understanding of the topography sensing mechanism with a special emphasis on the role of the nucleus. Here, recent techniques developed for monitoring the nuclear mechanics are reviewed and the impact of various topographies and their consequences on nuclear organization, gene regulation, and stem cell fate is summarized. The role of the cell nucleus as a sensor of cell‐scale topography is further discussed. Abstract : Topography is a prominent component of the cellular microenvironment. The discovery of the role of the nucleus in the cellular response to topography has been demonstrated very recently. This progress report outlines the recent knowledge in the topography sensing mechanism with a special emphasis on the role of the cell nucleus as a sensor of cell‐scale topography.